Effect of acupuncture on the gait disturbance and hemodynamic changes in the prefrontal cortex: a study protocol for a randomized controlled trial - Zhenmei Hong; Shuijing Zhang; Shuqing Zhang; Yuqi Zhao; Xiancong Ye; Xinxin Shu; Yufan Chen; Shuding Yan; Ruijie Ma (Frontiers in Neurology)
BackgroundAlzheimer’s disease (AD) is characterized by cognitive impairment and behavioral impairment. The gait of AD patients is attracting the increasing attention. The aim of this randomized controlled trial (RCT) is to explore the effect of acupuncture on the cognitive function, gait performance, and hemodynamic changes in the prefrontal cortices.MethodsIn this RCT, a total of 108 AD patients will be randomly assigned into acupuncture group or control group for 8 weeks. The primary outcome will be three-dimensional gait analysis and cerebral hemodynamics using functional near-infrared spectroscopy (fNIRS). Secondary outcomes will include Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Barthel Index (BI).DiscussionThis trial is expected to explore the effect of acupuncture on cognitive function, gait performance, and hemodynamic changes in the prefrontal cortices for AD patients.